Mauritius’ Competitive Party Politics and Social Democratic Welfare Outcomes after Independence (The Strategic Review for Southern Africa, 2020)
Mauritius has cast herself as an outlier on the African political landscape, having hosted peaceful, free and fair elections since the advent of independence in 1968 without fail. The island state of Mauritius, which lies over 2000km off the coast of East Africa, boasts a multiplicity of political parties which have added to the vibrancy of political culture in that country. Election season tends to be a hotly contested period in which various political parties, by virtue of their claims as custodians of collective and national centre left interests, jostle one another for dominance under the banner of pro-poor development. This essay considers Mauritius’ status as a social democratic welfare state by drawing the relation between the country’s competitive political culture and development successes against the backdrop of its democratic election experiences from 1968 to 2005. While election outcomes elsewhere on the continent tend to reflect the maturity of democratic spaces in which political spaces exist, in Mauritius they continue to serve as a litmus test to ascertain the level of commitment to the social cause by the ruling incumbents and aspirants alike.
Keywords: African political landscape; Mauritius; East Africa; political culture; pro-poor development; 1968 to 2005